Efektivitas Model PBL dan Discovery Learning Berbantuan Wolfram Mathematica Terhadap Kemampuan Literasi Numerasi Siswa - Prawitasuri, Chintya Dewi; Shodiqin, Ali; Prasetyowati, Dina (STAI Al-Bahjah, 2025)
This study aims to determine the effectiveness of the Problem Based Learning (PBL) and Discovery Learning (DL) learning models assisted by Wolfram Mathematica in improving students' numeracy literacy skills in the material of Relations and Functions. The study was conducted at SMP N 1 Winong involving three sample classes: class VIII E as experimental class 1 using Problem Based Learning (PBL), class VIII F as experimental class 2 using Discovery Learning (DL,) and class VIII G as a control class using conventional learning. Data collection techniques include numeracy literacy ability tests, observation of activity sheets and documentation. The results of the study indicate that (1) there are differences in students' numeracy literacy skills in the Problem Based Learning, Discovery Learning, and Conventional (Direct Learning) models; (2) students' numeracy literacy skills in the Problem Based Learning models are better than in the conventional learning models; (3) students' numeracy literacy skills in the Discovery Learning model are better than in conventional learning; (4) there is no significant difference in students' numeracy literacy skills in the Problem Based Learning and Discovery Learning models; (5) The influence of student activity on students' numeracy literacy skills is 70.8% for the Problem Based Learning model and 50.3% for the Discovery Learning model.